Investigation of carbapenemases and aminoglycoside modifying enzymes of Acinetobacter baumannii isolates recovered from patients admitted to intensive care units in a tertiary-care hospital in Brazil - Polotto, Milena (Rev Soc Bras Med Trop, 2019)
INTRODUCTION: Acinetobacter baumannii are opportunistic bacteria, highly capable of acquiring antimicrobial resistance through the production of carbapenemases and aminoglycoside modifying enzymes (AMEs). METHODS: Carbapenemase and AME genes were investigated in A. baumannii recovered from inpatients of a Brazilian hospital. RESULTS: The key genes found were bla (OXA-51-like,) the association ISAba1- bla (OXA-23-like), and the AME genes aph(3´)-VI, aac(6´)-Ib, aac(3)-Ia, and aph(3´)-Ia. Different clusters spread through the institution wards. CONCLUSIONS: The dissemination of bla (OXA-23-like) and AME-carrying A. baumannii through the hospital highlights the need for improved preventive measures to reduce the spread of infection.